Is rituximab effective for systemic sclerosis? A systematic review and meta-analysis - Marina Maria Vieira de Figueiredo Caldas (Advances in Rheumatology, 2021)
Abstract Background Systemic sclerosis (SSc) is a clinically complex and challenging disease, that leads to skin fibrosis. Its most frequent complication is interstitial lung disease (ILD), which leads to a worse prognosis. In this situation, cyclophosphamide is considered the gold standard for its treatment, despite the controversies regarding its efficacy and toxicity. However, studies using rituximab (RTX) have shown that this drug may be a promising therapeutic option. Objectives This paper objective was to analyze the scientific evidence on the RTX effects on SSc. Methods A systematic review (SR) was performed including clinical trials (CTs) on the use of RTX in SSc, published up to May 2020. The studies were identified through systematic searches in bibliographic databases using a predefined search strategy. The following databases were used: PUBMED, SCOPUS, SCIELO, LILACS, SCIENCE DIRECT, WEB OF SCIENCE, COCHRANE, WHOLIS, PAHO and EMBASE. Also, a manual search was performed. The methodological quality of the studies was determined using Jadad scale, Risk of Bias Tool (RoB 2.0) and Risk of Bias in Non-Randomized Studies - of Interventions tool (ROBINS-I). A meta-analysis of the randomized CTs was performed, using Review Manager. Results Ten CTs were included in this SR. Of these, three were randomized and seven were non-randomized. Five showed a statistically significant improvement in forced vital capacity (FVC) at some time during follow-up. Regarding the skin, eight studies showed statistically significant improvements according toa the modified Rodnan skin score. The meta-analysis found positive effects of RTX in SSc, with a statistical significance for lung disease. Conclusion Rituximab is a promising strategy for the SSc-associated ILD and cutaneous fibrosis treatment. PROSPERO registration number: CRD42019132018.